TRADITIONAL INDUSTRIES: UNLEASHING THE GROWTH POTENTIAL - State Planning Board, Government of Kerala
The traditional industries occupy a predominant position in Kerala’s economy. The vision is to transform these industries into modern and high value-added ones. Modernisation is essential for the development of the cashew industry sector. The handloom industry is a part of national heritage and hence will be promoted with the primary objective of preserving this ancient craft by protecting its dependents from the threat of power looms/ fully automatic looms / machineries. It will be a niche industry. Coir has many inherent advantages, but the industry is yet to achieve its real potential for want of an integrated approach. Continuous effort must be directed to new sources of income through product diversification and improved product quality, with emphasis on market-oriented technologies. This holds the most potential for Kerala.